Government Intervention, Perceived Benefit, and Bribery of Firms in Transitional China - Gao, Yongqiang (2011)
This article examines whether (1) government intervention causes bribery (or corruption) as rent-seeking theory suggested; (2) a firm’s perceived benefit partially mediates the relationship between government intervention and its bribing behavior, as rational choice/behavior theory suggested; and (3) other firms’ bribing behavior moderates the relationship between government intervention and a firm’s perceived benefit. Our study shows that government intervention causes bribery/corruption indeed, but it exerts its effect on bribery/corruption through the firm’s perceived benefit. In other words, a firm’s perceived benefit fully mediates the relationship between government intervention and its bribing behavior. We also find that other firms’ bribery positively moderates the relationship between government intervention and a given firm’s bribery. This study partly proves that firms are rational actors. Potential benefit encourages them to practice bribery. Besides, this research also supports the rent-seeking view of bribery/corruption, which argues that government intervention is a source of bribery/corruption. However, we have also identified that only those government interventions that will create “rent” can cause bribery/corruption.
Keywords: Transitional China; Perceived benefit; Mimetic isomorphism; Government Intervention; Bribery